Cautionary note on the use of Caenorhabditis elegans to study muscle phenotypes caused by mutations in the human MYH7 gene - Gil-Gálvez, Alejandro (BioTechniques, 2020)
Mutations in the human MYH7 gene, encoding a slow skeletal muscle/β-cardiac myosin heavy chain, cause different types of myopathies. The nematode model Caenorhabditis elegans has frequently been employed to study the molecular and physiological consequences of MYH7 mutations in muscle function by introducing mutations into the unc-54 gene, the worm MYH7 ortholog. We report here that the C. elegans model is not appropriate for such studies if they involve expression of the UNC-54 protein (wild-type or fused to green fluorescent protein) above endogenous levels